1984
DOI: 10.1029/jc089ic03p03550
|View full text |Cite
|
Sign up to set email alerts
|

Air‐ice drag coefficients for first‐year sea ice derived from aircraft measurements

Abstract: Turbulent flux measurements were made at four levels (42, 90, 195, and 340 m) by the NOAA P-3 aircraft over first-year sea ice in the northern Bering Sea during February 1982. Three profiles of momentum flux and mean wind were used to calculate an air-ice drag coefficient CD of 3.0 ___ .6 x 10 -3 referenced to a 10-m anemometer height. The boundary layer was slightly unstable (z.JL = -1.2, where z i was the inversion height of 660 m and L the Monin-Obukhov length). The mean wind speed at the 42-m height was 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The boundary layer requires time and distance to adjust to surface changes, hence acts like a low-pass filter to variations in roughness. The fact that local measurements of roughness [Macklin, 1983] and spatial averages over 40-km legs by aircraft [Walter et al, 1984]…”
Section: Discussionmentioning
confidence: 88%
“…The boundary layer requires time and distance to adjust to surface changes, hence acts like a low-pass filter to variations in roughness. The fact that local measurements of roughness [Macklin, 1983] and spatial averages over 40-km legs by aircraft [Walter et al, 1984]…”
Section: Discussionmentioning
confidence: 88%
“…where Pa is the air density and C ai is a drag coefficient. The drag coefficient at the air-ice interface (Cai) will be chosen to be twice as large as that at the air-water interface (Caw) but is still somewhat smaller than the measured value under slightly unstable atmospheric conditions [Walter et al, 1984]. In this application, U•o is either uniform or Gaussian, given by either where Pw is the seawater density and U is the surface ocean current.…”
Section: Tat--pacai U101u10 (3)mentioning
confidence: 99%
“…The drag coefficient at the air-ice interface (Cai) will be chosen to be twice as large as that at the air-water interface (Caw) but is still somewhat smaller than the measured value under slightly unstable atmospheric conditions [Walter et al, 1984]. …”
Section: Paper Number 1999jc900159mentioning
confidence: 99%
“…Aircraft are ideal platforms for quickly obtaining detailed spatial information on atmospheric structure and dynamics. However, since the covariance technique to determine wind stress usually requires averaging over a path length of at least 30 km [e.g., Walter et al, 1984;Fairall and Markson, 1987;Walter and Overland, 1991] Over open ocean there was also a sloping inversion, but a horizontal temperature gradient within the ABL counteracted the baroclinic effect at the surface, resulting in a factor B value of 1.00. Kellner et al [1987] found that the wind stress in the region just inside the ice edge over was about 40% lower than the open ocean (Table 1 and Figure 1, curve 2), based on an aircraft flight during slightly off-ice winds in the Fram Strait MIZ on July 7, 1984.…”
Section: Aircraft Measurementsmentioning
confidence: 99%